Religion as a Socializing Force in the "Woman Question" - Mananzan, OSB, Sr. Mary John (Review of Women's Studies; Vol 9 No 1-2 (1999): Review of Women's Studies Volume IX, Numbers 1-2 (January-December 1999), 2000)
---